Pro-angiogenic Role of Danqi Pill Through Activating Fatty Acids Oxidation Pathway Against Coronary Artery Disease - Jiao, Shihong; Tang, Binghua; Wang, Yong; Li, Chun; Zeng, Zifan; Cui, Lixia; Zhang, Xuefeng; Shao, Mingyan; Guo, Dongqing; Wang, Qiyan (Frontiers in Pharmacology, 2018)
Coronary artery disease (CAD) is one of the leading causes of deaths worldwide. Energy metabolism disorders, including a reduction in fatty acids oxidation and upregulation of glycolysis pathway, are involved in the process of CAD. Therapeutic angiogenesis has become a promising treatment for CAD. Traditional Chinese medicines, such as Danqi Pill (DQP), have been proven to be effective in treating CAD in China for many years. However, the pro-angiogenic effects of DQP based on fatty acids oxidation are still unknown and the mechanism is worthy of investigation. In this study, left anterior descending (LAD) coronary artery was ligated to induce the coronary artery disease models in vivo, and cardiac functions were examined using echocardiography. Human umbilical vein endothelial cells (HUVEC) were subjected to H2O2-induced oxidative stress in vitro. The effects of DQP on CAD rat models and in vitro HUVEC were detected. Our results showed that DQP had cardio-protective effects in rat model. The intensity of capillaries in the marginal area of infarction of the rat heart was increased remarkably in DQP group, and the expression of PPARα and VEGF-2 were increased. The key enzymes involved in the transportation and intake of fatty acids, including CPT1A and CD36, both increased. In H2O2-induced endothelial cells injury models, DQP also showed protective roles and promoted capillary-like tube formation. DQP up-regulated key enzymes in fatty acids oxidation in H2O2-treated HUVEC. In addition, inhibition of CPT1A compromised the pro-angiogenic effects of DQP. In conclusion, fatty acids oxidation axis PPARα-CD36-CPT1A was involved in the pro-angiogenic roles of DQP against CAD. Cardiac CPT1A may serve as a target in therapeutic angiogenesis in clinics.